WAYS OF INNOVATIVE DEVELOPMENT OF AGRICULTURE AND IMPROVEMENT OF PRODUCT COMPETITIVENESS IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article explores innovative development of agriculture and ways to increase product competitiveness in the digital economy. Also, the factors affecting the sustainable development of agriculture through innovative activities, the technological, technical, and organizational-economic competitiveness of the production base in agriculture as a result of assimilation of knowledge and innovations are substantiated in the article.